Education Management and its Financing - Đurić, Igor R. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
An increased scientific interest in studying different models of education management systems is conditioned by the fact that the quality of education depends significantly on the management style. Thus, the process of creation of efficient systems of management and financing of the education presents a priority in educational policies of contemporary societies. The paper analyses different approaches to the education management systems in some European countries, on the comparative basis, with the aim of achieving as much of a total insight into contemporary courses of such processes as possible. The results of analysis show that the traditional division into centralized and decentralized systems of management is relativized, with a tendency to achieve an optimal relationship among different subjects in the process of management on the central, regional and local level of authority.
Keywords: education; decentralization of education; system of education financing; models of education management